Interventions to improve healthcare workers' hand hygiene compliance: A systematic review of systematic reviews. (11th December 2018) - Price, Lesley; MacDonald, Jennifer; Gozdzielewska, Lucyna; Howe, Tracey; Flowers, Paul; Shepherd, Lesley; Watt, Yvonne; Reilly, Jacqui
Abstract: Objective: To synthesize the existing evidence base of systematic reviews of interventions to improve healthcare worker (HCW) hand hygiene compliance (HHC). Methods: PRISMA guidelines were followed, and 10 information sources were searched in September 2017, with no limits to language or date of publication, and papers were screened against inclusion criteria for relevance. Data were extracted and risk of bias was assessed. Results: Overall, 19 systematic reviews (n=20 articles) were included. Only 1 article had a low risk of bias. Moreover, 15 systematic reviews showed positive effects of interventions on HCW HHC, whereas 3 reviews evaluating monitoring technology did not. Findings regarding whether multimodal rather than single interventions are preferable were inconclusive. Targeting social influence, attitude, self-efficacy, and intention were associated with greater effectiveness. No clear link emerged between how educational interventions were delivered and effectiveness. Conclusions: This is the first systematic review of systematic reviews of interventions to improve HCW HHC. The evidence is sufficient to recommend the implementation of interventions to improve HCW HHC (except for monitoring technology), but it is insufficient to make specific recommendations regarding the content or how the content should be delivered. Future research should rigorously apply behavior change theory, and recommendations should be clearly described with respect to intervention content and how it is delivered. Such recommendations should be tested for longer terms using stronger study designs with clearly defined outcomes.